Dinamika Kependudukan dan Dampaknya Terhadap Lingkungan - Nurhayani Nurhayani; Rabiatul Alya; Glenn Hosea Fernando Ringkat; Yusawinur Barella (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This study discusses population parameters and environmental parameters as two interrelated concepts and are very important in understanding population dynamics and environmental quality in a region. Population parameters involve calculating the number of populations to determine the rate of population growth, which is influenced by factors such as population, birth rate, death rate, and migration rate. Meanwhile, environmental parameters are used to determine environmental quality, including air quality, water quality, and climate change. This research emphasizes the importance of a comprehensive analysis of these two parameters for the development of sustainable and environmentally sound policies. The close relationship between population and environmental parameters suggests that changes in one parameter can affect the other. Therefore, this study aims to explore the interaction between population and environmental parameters and their implications for development planning and natural resource conservation.This study discusses population parameters and environmental parameters as two interrelated concepts and are very important in understanding population dynamics and environmental quality in a region. Population parameters involve calculating the number of populations to determine the rate of population growth, which is influenced by factors such as population, birth rate, death rate, and migration rate. Meanwhile, environmental parameters are used to determine environmental quality, including air quality, water quality, and climate change. This research emphasizes the importance of a comprehensive analysis of these two parameters for the development of sustainable and environmentally sound policies. The close relationship between population and environmental parameters suggests that changes in one parameter can affect the other. Therefore, this study aims to explore the interaction between population and environmental parameters and their implications for development planning and natural resource conservation.